Will drug resistance against dolutegravir in initial therapy ever occur? - Wainberg, Mark A.; Han, Ying-Shan (Frontiers in Pharmacology, 2015)
Dolutegravir (DTG) is a second-generation integrase strand transfer inhibitor (INSTI) and INSTIs are the latest class of potent anti-HIV drugs. Compared to the first generation INSTIs, raltegravir, and elvitegravir, DTG shows a limited cross-resistance profile. More interestingly, clinical resistance mutations to DTG in treatment-naive patents have not been observed to this date. This review summarizes recent studies on resistance mutations to DTG and on our understanding of the mechanisms of resistance to DTG as well as future directions for research.